Classroom Management: Improving Students Learning Outcome through Project-Based Learning - Muhria, Lanlan; Syarifudin, Aip; Wiarsih, Asih (Annpublisher, 2024)
This research aims to determine project-based learning class management in improving students' English learning outcomes. Therefore, the method used in this research is classroom action research using two cycles. The study's findings indicate that using a project-based learning approach can enhance students' learning outcomes in English classes. The student's learning outcomes in the second cycle demonstrate this; they received an A grade of 33%, above the learning objective/completion by 30%; a B value of 50%, matching the aim of 50%; and a C grade of 17%, well below the target of 20%.